A comparative study of metformin and glyburide in gestational diabetes mellitus - Pujara, Prashant; Singh, Vinita; Murmu, Sunita; Kumari, Suman; Prajapati, Dhara (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Incidence of gestational diabetes mellitus (GDM) is increasing worldwide. GDM provides a window of opportunity for the primary prevention of the type 2 diabetes by preventing transgeneration transmission to fetus. Insulin in management of GDM has many drawbacks, so use of OHAs has been increased worldwide. Methods: Randomized control trial was performed in patients with GDM who required medical management. Subjects were randomized into two groups and treated with Metformin and Glyburide, results were compared. Results: While comparing efficacy of metformin and glyburide in this study for maternal variables; the failure rate of metformin was found to be 9.39 times higher compared to glyburide. Glyburide was associated with 9.5 times more risk to develop hypoglycemia in mother compared to metformin. While comparing neonatal variables nursery admission was found to be more and statistically significant in neonates whose mother has received glyburide compared to metformin (p=0.03, RR=2.26). Though statistically insignificant, LGA fetuses and neonatal hypoglycemia were 2.1 times more in glyburide group compared to metformin. Conclusions: Though glyburide can be effective alternative to metformin and insulin for GDM, it is associated with higher risk of maternal hypoglycemia, neonatal hypoglycemia, LGA fetuses and higher rate of nursery admissions compared to metformin. Higher adverse neonatal outcomes with glyburide use question the widespread use of glyburide as first line management modality in GDM and also as an alternative to insulin as advised by many groups.